Efficacy of Iopamidol for Sealing an Injured Thoracic Duct: Pilot Experiments in a Large Animal - Hyo Yeong Ahn (Applied Sciences, 2020)
Chylothorax can be spontaneously healed by lymphangiography using lipiodol, but pulmonary or systemic embolization is a potential complication. We determined the efficacy of iopamidol for treating chylous leakage in an animal model. Twelve pigs were randomly divided into two groups. After inducing thoracic duct damage, pigs from groups A and B were injected with iopamidol and lipiodol, respectively. At 5, 10, and 30 min after damage induction, the drug effects were monitored by video-assisted thoracoscopy and lymphangiography. In vitro, chyle samples from the pigs were incubated with iopamidol and lipiodol. The damaged thoracic duct was harvested and examined using microscopy. In group A, four and two pigs did not show chylous leakage after 5 and 10 min, respectively. In group B, none showed chylous leakage after 5 min. Nevertheless, the p value was 0.46, and there was no statistically significant difference between groups A and B. In vitro, both iopamidol- and lipiodol-treated chyle samples adhered after 5 min and solidified at 30 min. Our findings confirmed that the damaged thoracic duct was clogged with an amorphous proteinaceous material (iopamidol). Therefore, iopamidol is potentially a new therapeutic agent for chylous leakage. Thoracic duct embolization failures or systemic embolization risks from lipiodol injection may be avoided by injecting iopamidol via the thoracic duct, and this warrants further investigation.